Native kidney cytomegalovirus nephritis and cytomegalovirus prostatitis in a kidney transplant recipient. Issue 1 (28th September 2018) - Tan, Susanna K.; Cheng, Xingxing S.; Kao, Chia‐Sui; Weber, Jenna; Pinsky, Benjamin A.; Gill, Harcharan S.; Busque, Stephan; Subramanian, Aruna K.; Tan, Jane C.
Abstract: We present a case of cytomegalovirus (CMV) native kidney nephritis and prostatitis in a CMV D+/R‐ kidney transplant recipient who had completed six months of CMV prophylaxis four weeks prior to the diagnosis of genitourinary CMV disease. The patient had a history of benign prostatic hypertrophy and urinary retention that required self‐catheterization to relieve high post‐voiding residual volumes. At 7 months post‐transplant, he was found to have a urinary tract infection, moderate hydronephrosis of the transplanted kidney, and severe hydroureteronephrosis of the native left kidney and ureter, and underwent native left nephrectomy and transurethral resection of the prostate. Histopathologic examination of kidney and prostate tissue revealed CMV inclusions consistent with invasive CMV disease. This case highlights that CMV may extend beyond the kidney allograft to involve other parts of the genitourinary tract, including the native kidneys and prostate. Furthermore, we highlight the tissue‐specific risk factors that preceded CMV tissue invasion. In addition to concurrent diagnoses, health care providers should have a low threshold for considering late‐onset CMV disease in high‐risk solid organ transplant recipients presenting with signs and symptoms of genitourinary tract pathology.